Applied numerical methods with MATLAB : for engineers and scientists - Chapra, Steven C. (New York, NY : McGraw Hill Education, 2023)
'This book is designed to support a one-semester course in numerical methods. It has been written for students who want to learn and apply numerical methods in order to solve problems in engineering and science. As such, the methods are motivated by problems rather than by mathematics. That said, sufficient theory is provided so that students come away with insight into the techniques and their shortcomings'--
Includes bibliographical references and index.
Keywords: Numerical analysis -- Data processing -- Textbooks; MATLAB -- Textbooks; Engineering mathematics -- Textbooks